The cytoprotective sequestration activity of small heat shock proteins is evolutionarily conserved - Shrivastava, Aseem; Sandhof, Carl Alexander; Reinle, Kevin; Jawed, Areeb; Ruger-Herreros, Carmen; Schwarz, Dominic; Creamer, Declan; Nussbaum-Krammer, Carmen; Mogk, Axel; Bukau, Bernd (The journal of cell biology, 2022)
The chaperone-mediated sequestration of misfolded proteins into inclusions is a pivotal cellular strategy to maintain proteostasis in Saccharomyces cerevisiae, executed by small heat shock proteins (sHsps) Hsp42 and Btn2. Direct homologs of Hsp42 and Btn2 are absent in other organisms, questioning whether sequestration represents a conserved proteostasis strategy and, if so, which factors are involved. We examined sHsps from Escherchia coli, Caenorhabditis elegans, and humans for their ability to complement the defects of yeast sequestrase mutants. We show that sequestration of misfolded proteins is an original and widespread activity among sHsps executed by specific family members. Sequestrase positive C. elegans’ sHsps harbor specific sequence features, including a high content of aromatic and methionine residues in disordered N-terminal extensions. Those sHsps buffer limitations in Hsp70 capacity in C. elegans WT animals and are upregulated in long-lived daf-2 mutants, contributing to lifespan extension. Cellular protection by sequestration of misfolded proteins is, therefore, an evolutionarily conserved activity of the sHsp family.